Contemporary Trends in Adjuvant and Neoadjuvant Treatment for Renal Cell Carcinoma - ÇAM, HAYDAR KAMİL (GALENOS YAYINCILIK, 2018)
Renal cell carcinoma is an increasingly significant cancer in which surgical resection is still the sole curative approach. There is a risk of recurrence in one-third of patients after surgery. Successful experiences with some solid organ cancers and effective treatment response to targeted agents in metastatic cases have suggested a similar adjuvant approach for renal cell carcinoma. Consequently, placebo-controlled adjuvant trials have been reported and the Food and Drug Administration approved sunutinib as an adjuvant treatment after nephrectomy in high-risk patients, with the risk of treatment-related side effects. Several clinical series have indicated that neoadjuvant application can provide significant downsizing of the cancer mass in complex cases and enable radical surgery. Similarly, neoadjuvant therapy could enable nephron-sparing surgery for certain patients. Both adjuvant and neoadjuvant approaches for renal cell carcinoma require further trials with larger patient numbers. This review presents contemporary experience on adjuvant and neoadjuvant treatment for renal cell carcinoma.
Keywords: Renal cell carcinoma; adjuvant; neoadjuvant; targeted therapy; TARGETED MOLECULAR THERAPIES; RADICAL NEPHRECTOMY; PHASE-III; CLINICAL-TRIALS; STAGE-II; RISK; SUNITINIB; CANCER; SURGERY; SORAFENIB